2018 IEEE Symposium on Computers and Communications (ISCC) 2018
DOI: 10.1109/iscc.2018.8538521
|View full text |Cite
|
Sign up to set email alerts
|

Modest BBR: Enabling Better Fairness for BBR Congestion Control

Abstract: As a vital component of TCP, congestion control defines TCP's performance characteristics. Hence, it is important for congestion control to provide high link utilization and low queuing delay. Recent BBR tries to estimate available bottleneck capacity to achieve this goal. However, its aggressiveness characteristics generate a massive amount of packet retransmission which harms loss-based congestion control protocol such as Cubic. In this paper, we first dive into this issue and reveal that the aggressiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Because BBR is a work in progress, many issues [5]- [9] were reported for the initial BBR v1 announced by Google. One of the serious issues is throughput imbalance due to the RTT differences of BBR flows.…”
Section: Thus New Congestion Control Algorithms Based On Variousmentioning
confidence: 99%
See 1 more Smart Citation
“…Because BBR is a work in progress, many issues [5]- [9] were reported for the initial BBR v1 announced by Google. One of the serious issues is throughput imbalance due to the RTT differences of BBR flows.…”
Section: Thus New Congestion Control Algorithms Based On Variousmentioning
confidence: 99%
“…Sasaki et al [17] Miyazawa et al [18] examined fairness between CUBIC and BBR and found extreme inter-protocol throughput imbalances and periodic throughput variations when coexisting with CUBIC. Zhang et al [9] proposed Modest BBR to mitigate the aggressiveness of BBR when the bottleneck buffer is small. BBR was modified to be sensitive to packet loss, reducing the sending rate based on loss so the CUBIC flow could use the proper bandwidth.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, the extensive research has been conducted to further improve the performance of BBR [24][25][26][27][28][29][30]. Moreover, Google has been actively working on developing BBR v2, an improved version of the current BBR v1 [31].…”
Section: A Brief Overview Of Bbrmentioning
confidence: 99%
“…Because BBR is still in the development stage, fairness between BBR algorithm and other loss-based CCAs [ 26 , 27 , 28 , 29 ] and RTT fairness [ 12 , 30 , 31 , 32 , 33 , 34 ] need to be improved. In the above analysis, one of the most serious problems of BBR is the RTT fairness problem in the protocol.…”
Section: Introductionmentioning
confidence: 99%